Comparison between Keros and Gera Classifications on Paranasal Sinuses Computed Tomography Scan in One Teaching Hospital in Medan, Indonesia - Nasution, Fingga Prahasti; Daulay, Elvita Rahmi; Sofyan, Ferryan (Althea Medical Journal, 2025)
Background: Functional endoscopic sinus surgery (FESS) is a surgical procedure for chronic rhinosinusitis (CRS). Keros and Gera classification can be used to evaluate the height and angle of the lateral lamella (LL) on computed tomography (CT) scan of the paranasal sinuses (PNS) which is the most dangerous area and at risk of injury during FESS. This study aimed to analyze the difference between Keros and Gera classifications on CT scans of PNS.Methods: This study was a cross-sectional study using the results of PNS CT scans from 94 patients at Prof. Dr. Chairuddin Panusunan Lubis Universitas Sumatera Utara Hospital, Medan, Indonesia for the period January–December 2022. The Keros and Gera classification of PNS CT scan were compared based on age and gender and then analyzed using the Chi-Square test. The results were significant if the p-value < 0.05.Results: The most common type of right-sided Keros classification was type 2 (54.3%) and left-sided was type 1 (56%), while the most common type of right-sided and left-sided Gera classification were type 2 (67% and 80.8%). A significant difference was found between the Keros and Gera classification types (p <0.001).  The higher the Keros type did not guarantee the higher Gera type, each type of Keros could be paired with each type of Gera.Conclusions: There is a significant difference between Keros and Gera classification on the results of PNS CT scan of patients. Keros classification alone is not enough to identify the high-risk areas at the skull base, therefore, a combination with Gera classification needs to be evaluated by a radiologist to help the clinician in planning a safer FESS.